1986
DOI: 10.1109/t-uffc.1986.26836
|View full text |Cite
|
Sign up to set email alerts
|

High-Coupling and High-Velocity SAW Using ZnO and AlN Films on a Glass Substrate

Abstract: The characteristics of surface acoustic waves propagating on a three-layered structure consists of a piezoelectric ZnO film, a piezoelectric AIN film, and a Kovar glass sheet have been studied. Both theoretical and experimental results have shown that the first-mode leaky surface acoustic wave has a high volocity (V,,), a high coupling coefficient ( k ' ) , a small temperature coefficient of frequency (TCF), and a tolerably small propagation loss (PL) when the product of the wavenumber and the film thickness (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Elastic wave propagation in layered piezoelectric media are given to considerable attention previously exhibited by the literature of Pauley and Dong (1976), Shiosai et al (1986), Siao and Dong (1994) and Wang and Quek (2001). Furthermore, there have also been many works about wave characteristics and transient response of FGM structures.…”
Section: Introductionmentioning
confidence: 99%
“…Elastic wave propagation in layered piezoelectric media are given to considerable attention previously exhibited by the literature of Pauley and Dong (1976), Shiosai et al (1986), Siao and Dong (1994) and Wang and Quek (2001). Furthermore, there have also been many works about wave characteristics and transient response of FGM structures.…”
Section: Introductionmentioning
confidence: 99%
“…This is probably due to the unavailability of precise temperature elastic constants of AlN film. Furthermore, some contradictions were recorded, and we found in the literature that the TCF value of AlN film is either positive [18] or negative [21,22]. So, at the moment, the behavior of TCF of high frequency SAW devices based on AlN/diamond layered structure remains still unclear.…”
Section: IIImentioning
confidence: 97%
“…One can observe that the TCF increases in the kh range between 2 and 3, exhibiting a value between -21ppm/°C and -9ppm/°C. In this range, the wavelength decreases meaning that the acoustic waves are more confined in the AlN film, and consequently, the TCF of AlN film, which is positive [18], while the TCF of diamond layer is negative [19][20], affects more the TCF of AlN/diamond layered structure. However, in the kh range between 3 and 5.24, the measured TCF decreases from9ppm/°C and -20ppm/°C.…”
Section: IIImentioning
confidence: 99%
“…The effect of the LSAW on the frequency of SAW filters was attributed to the spatial variations in the density of the glass substrate, and the problem was surmounted by an appropriate heat treatment of the glass at the glass production stage itself. Despite the successful application of ZnO films in SAW devices on glass for the 30-60-MHz range, i.e., SAW filters for video intermediate frequency (VIF) stage in TV/VCR equipment [3]- [8], efforts are still continuing for further improvements in functional performance of the devices [9]. Minimizing the insertion loss and improving the temperature stability [10] are of particular interest for establishing good quality control.…”
Section: Introductionmentioning
confidence: 99%
“…Nakagawa [5] reported that the TCD could be reduced to zero with ZnO film thickness = 0.27 λ for a 65-MHz device fabricated with ZnO/pyrex glass having interdigital transducer (IDT) electrodes underneath the sputtered ZnO film. Shiosaki et al interfaced ZnO and AlN films having opposite TCD characteristics on a special Kovar glass sheet having SiO 2 as the main component [8], and by increasing the thickness of the underlying AlN layer to 0.8 λ underneath a fixed ZnO film thickness of 0.16 λ; the TCD could be reduced only to −10 ppm · • C −1 from −40 ppm · • C −1 .…”
Section: Introductionmentioning
confidence: 99%